2013
DOI: 10.1016/j.envres.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Temperature, nitrogen dioxide, circulating respiratory viruses and acute upper respiratory infections among children in Taipei, Taiwan: A population-based study

Abstract: Current study suggested a positive association between outpatient visits for acute upper respiratory infections and ambient environment factors, including average temperature, air pollutants, and circulating respiratory viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 41 publications
5
38
1
2
Order By: Relevance
“…Approximately 85 % of outpatient visits of respiratory diseases are acute upper respiratory infections (ICD9 CM 460-466) and 9.8 % of patients are for pneumonia and influenza in Taiwan (Department of Health 2011). Therefore, the finding in this study agrees with previous reports that higher risks of respiratory infections are associated with low temperatures (Falagas et al 2008;Makinen et al 2009;Liao et al 2009;Lin et al 2013b). Lin et al (2009) evaluated the associations between hospital admissions for respiratory diseases and extreme high temperature in New York City.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Approximately 85 % of outpatient visits of respiratory diseases are acute upper respiratory infections (ICD9 CM 460-466) and 9.8 % of patients are for pneumonia and influenza in Taiwan (Department of Health 2011). Therefore, the finding in this study agrees with previous reports that higher risks of respiratory infections are associated with low temperatures (Falagas et al 2008;Makinen et al 2009;Liao et al 2009;Lin et al 2013b). Lin et al (2009) evaluated the associations between hospital admissions for respiratory diseases and extreme high temperature in New York City.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, Wong et al (2006) have also identified NO 2 with the greatest effects, followed by O 3 on acute upper respiratory infections. However, Lin et al (2013b) have recently related lower temperature, instead of respiratory viruses and ambient air pollutants, to the greatest risk change of outpatient visits for acute upper respiratory infections in Taipei, Taiwan.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…High temperatures or heat can cause fatigue in humans because the heat causes a lot of sweat to be released, so it becomes dehydrated. Likewise with children and toddlers can be affected by flu, cough, runny nose, fever, respiratory tract disorders, colds, digestive disorders, allergies, and the most dangerous is Upper Respiratory Tract Infection [18]. Also, the increase in environmental temperature will also affect the impact of air pollution, especially in urban areas and affect individuals with chronic diseases such as heart disease, asthma and other respiratory diseases [19].…”
Section: Discussionmentioning
confidence: 99%